Exploration of potential wild medicinal mushrooms from Pocut Meurah Intan forest park, Aceh, Indonesia - HENDRIX INDRA KUSUMA; ESSY HARNELLY; ZAIRIN THOMY; MUHAMMAD ADRIYAN FITRA; SAMINGAN SAMINGAN (Universitas Syiah Kuala, 2020)
Mushroom is one of living things with abundant diversity and has various beneficial potentials; one of them is as medicine. The use of mushrooms as medicine has long been known primarily as traditionally made herbs and the knowledge has been passed down for generations. The Pocut Meurah Intan Forest Park as a conservation forest, stores a variety of mushrooms in it. Data about the type of mushroom that has medicinal potential existed in the forest park has never been published so it is important to do so. This study aims to record the types of mushrooms that have benefits as medicines. The method used is an exploratory survey through a trail or tracking path then identified as a medicinal mushroom base on literature studies. The results of the study found 15 species of mushrooms that have potential as medicine, namely Cookeina tricholoma, Sarcoscypha coccinea, Tremella fuciformis, Auricularia auricula-judae, Flammulina velutipes, Schizophyllum commune, Scleroderma citrinum, Boletus edulis, Trametes versicolor, Lentinus tigrinus, Lentinus squarosulus, Ganoderma applanatum, Ganoderma resinaceum, Thelephora ganbajun and Lycoperdon echinatum. This shows that Pocut Meurah Intan Forest Park has great resources and potential that can be utilized for the benefit of the surrounding community, and it needs to be preserved so that diversity is maintained and can be used by future generations.